Translational control of lipogenic enzymes in the cell cycle of synchronous, growing yeast cells. (5th January 2017) - Blank, Heidi M; Perez, Ricardo; He, Chong; Maitra, Nairita; Metz, Richard; Hill, Joshua; Lin, Yuhong; Johnson, Charles D; Bankaitis, Vytas A; Kennedy, Brian K; Aramayo, Rodolfo; Polymenis, Michael
Abstract: Translational control during cell division determines when cells start a new cell cycle, how fast they complete it, the number of successive divisions, and how cells coordinate proliferation with available nutrients. The translational efficiencies of mRNAs in cells progressing synchronously through the mitotic cell cycle, while preserving the coupling of cell division with cell growth, remain uninvestigated. We now report comprehensive ribosome profiling of a yeast cell size series from the time of cell birth, to identify mRNAs under periodic translational control. The data reveal coordinate translational activation of mRNAs encoding lipogenic enzymes late in the cell cycle including Acc1p, the rate‐limiting enzyme acetyl‐CoA carboxylase. An upstream open reading frame (uORF) confers the translational control of ACC1 and adjusts Acc1p protein levels in different nutrients. The ACC1 uORF is relevant for cell division because its ablation delays cell cycle progression, reduces cell size, and suppresses the replicative longevity of cells lacking the Sch9p protein kinase regulator of ribosome biogenesis. These findings establish an unexpected relationship between lipogenesis and protein synthesis in mitotic cell divisions. Synopsis: Ribosome profiling reveals the coordinated translational activation of lipogenic enzyme transcripts in growing, unperturbed budding yeast cells progressing synchronously through the cell cycle. Translational control increases the levels of lipogenic enzymes late in the cell cycle. An upstream ORF in the ACC1 mRNA, which encodes the rate‐limiting enzyme acetyl‐CoA carboxylase, confers the translational control of ACC1 in the cell cycle and in response to nutrients. Translational control may link two fundamental aspects of cell growth: increase in protein mass and membrane surface. Abstract : Ribosome profiling reveals the coordinated translational activation of lipogenic enzyme transcripts in growing, unperturbed budding yeast cells progressing synchronously through the cell cycle.